Troubles and Determinants in Using ATMs. An exploratory study of a sample clients opinions of the Iraqi Trade Bank - Dhi Qar branch - Chitheer Mezaal, Wafaa; Abdulkhudhur Sukkar Alothman, Husham (Technium Social Sciences Journal, 2022)
This study aimed to shed light on the most prominent problems and obstacles facing the ATM users by applying to the clients of the Iraqi Trade Bank / Dhi Qar branch, and in order to achieve that goal the researchers designed a questionnaire directed to a sample of the clients of the Iraqi Trade Bank / Dhi Qar branch as a tool To collect data and to know their opinions regarding the ATM experience, the statistical program (SPSS) has been used in analyzing the results and through a number of statistical methods such as frequency distributions, percentages, mean, and standard deviation in order to prove the study hypotheses, and after study and analysis was completed Pray to a set of conclusions, the most important of which is that the large number of malfunctions to which the ATM machines are exposed and the lack of continuous cash flow negatively affect the bank's customers, and then a number of recommendations were suggested, the most prominent of which was the necessity to take all necessary measures to continue the work of the ATM Through continuous maintenance for it and the appointment of employees of the specialist to repair repeated faults, as well as providing cash liquidity at all times, specifically during the period of employee salaries.